Consumer purchase preferences towards foreign and domestic branded electrical appliances / Tan Shuan Gin and Susan Chin Tee Suan - Tan, Shuan Gin; Chin, Susan Tee Suan (2012)
The purpose of this study is to examine the consumer purchase preferences towards foreign and domestic branded electrical appliances. A total of 200 respondents took part in this survey. It was found that country of origin plays an important aspect in the purchase behaviour of the consumer.